The Influence of Motivation and Job Satisfaction on Employee Performance at the Immigration Office 1 Makassar - Deky Deky; Baharuddin Baharuddin; Hendrik Gunadi (Penerbit Goodwood, 2026)
Purpose: This study analyzes the effect of work motivation and job satisfaction on employee performance at Class I Immigration Office TPI Makassar. Increasing public demand and dynamic service transformation require continuous improvement in service quality. Research/Methodology: This study used an explanatory quantitative design with a saturated sample of 40 employees. Data were collected using structured Likert-scale questionnaires and analyzed using partial and simultaneous regression tests. Results/findings: Descriptive analysis categorized work motivation, job satisfaction, and performance as “good.” The partial test revealed that work motivation had no significant effect on performance, whereas job satisfaction had a significant positive effect. Simultaneously, motivation and satisfaction significantly influenced employee performance. Conclusions: Job satisfaction exerts a stronger influence than motivation on performance at the Immigration Office. Improvements in the work environment, recognition, and career development are likely to enhance employee outcomes. Limitations: The small sample size from a single government office limits the generalizability of the findings. Broader comparative research across institutions is recommended to strengthen external validity. Contributions: This study adds to the public sector human resource management literature by highlighting the greater impact of job satisfaction over motivation in shaping performance. It offers practical guidance for leaders to prioritize satisfaction-driven strategies to optimize employee performance.